Optic nerve sheath diameter is associated with postoperative delirium in patients undergoing open heart surgery - Aynur Kaynar; Özgür Kömürcü; Esma Bahşi; Ahmet Ozan Aydın; İlker Hasan Karal; Dilan Akyurt; Serkan Tulgar; Mustafa Süren (BMC Anesthesiology)
Abstract Background Increased intracranial pressure is a possible cause of postoperative delirium in open heart surgery patients. Optic nerve sheath diameter is a non-invasive measurement method used to monitor intracranial pressure changes. The authors suggested in this study that optic nerve sheath diameter monitoring could identify patients at risk of postoperative delirium. Method This prospective observational study was conducted by evaluating data from 90 patients undergoing open heart surgery. Optic nerve sheath diameter in patients was recorded before and after anesthesia induction, before and after cardiopulmonary bypass, and after intensive care transfer. Postoperative delirium was evaluated with the Confusion Assessment Method for the Intensive Care Unit scale. Results The study was completed with 90 patients and postoperative delirium was observed in 20 of the patients (22.2%). Optic nerve sheath diameter (OR, 5.787; 95% CI, 1.489–22.496; P = 0.011), history of alcohol use (OR, 6.032; 95% CI, 1.052–34.604; P = 0.044), and EuroSCORE II (OR, 3.090; 95% CI, 1.453–6.571; P = 0.003) was associated with postoperative delirium. Conclusions Optic nerve sheath diameter measured by ultrasonography is associated with postoperative delirium. The increase in optic nerve sheath diameter can be used predictively for postoperative delirium in open heart surgery. Trial registration Samsun University Samsun Training and Research Hospital, following ethics committee approval (Samsun University clinical research ethics committee (KAEK) 2023 11/7) and Clinical Trials (NCT05942183 / 05.09.2024) registration.